Correspondance vols. 1-6 - Proust, Marcel 1871-1922; Kolb, Philip 1907-1992 (Paris Plon, 1970)
Proust did not intend his correspondence to be published. His letters were above all a means of communication. Many of them are the equivalent of what today would be the subject of a telephone or electronic message. Because Proust, having very fine social skills and little practical sense, the most banal motives such as an invitation to dinner can be accompanied by long and subtle diplomatic explanations. Some letters are humorous, others express deep distress. Proust shows himself there as he appeared to his contemporaries: sensitive and intelligent, often charming, sometimes exasperating. From the moment Proust devoted himself to the composition of his novel, imposing long periods of seclusion on himself, his correspondence became a means of maintaining emotional and social ties.As Proust never kept a diary, his letters are the most important surviving document of his life and writing career. They make it possible to follow the development of his literary work and to identify the sources of inspiration in reality. By the diversity and number of its recipients, Proust's correspondence is also a wonderful documentary source on Parisian society and French culture at the turn of the century. Among other current topics, we find mentioned the Dreyfus affair, the trial of Oscar Wilde, the separation of Church and State, the First World War, Wagner, the Ballets Russes, the Dada movement, the theory of relativity.After Proust's death, his brother, Robert Proust, brought out six volumes of letters (Correspondance générale de Marcel Proust, Paris: Plon, 1930-1936). Some correspondents of Proust, such as Lucien Daudet or Georges de Lauris, edited the letters they had kept. Philip Kolb took up this task in a systematic and rigorous way, trying to date the letters (which, for the most part, are not) and to establish the text from the original. He first published several separate collections: Correspondance with his mother (1953), Marcel Proust and Jacques Rivière: Correspondance (1955), Letters to Reynaldo Hahn (1956), Letters found (1966). In 1970, the first volume of the Correspondance of Marcel Proust appeared with Plon, established, dated and annotated by Philip Kolb. The twenty-first and final volume appeared in 1993, a few months after Philip Kolb's death. In this edition, the letters are arranged in chronological order; each volume, except the first two which go from 1880 to 1901, covers one or two years.If Philip Kolb managed, like Proust, to complete the work of his life, he was well aware of having collected only a part of Proust's letters. A number of letters, belonging to the heirs of the recipients or to collectors, are still unpublished. Proust's letters are today among the most valued on the French autograph market. The National Library and some European and American libraries have collections of letters. The University of Illinois at Urbana-Champaign has about 1100 letters.
vol. 6: 1906
6 out of 21 volumes
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Correspondence; Literature; Paris (France)